(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
Stratigraphic and sedimentologic studies of the norian succession outcropping in rhe Lombardy Basin allowed the reconstruction of the paleogeographic and strucural evolution oi this area, 1) restricted lagoon and tidal flat are the most common deposits ar the Carnian-Norian boundary (Lower Member of the Dolomia Principale); 2) these are overlain by a thick inner platform succession organized in shallowing upwards cycles (lower Dolomia Principale), with the exception of Idro Lake area where intraplatform basin already generated; 3) the overlying middle-upper Dolomia Principale is dissected by synsedimentary faults with subsequent widespread development of intraplatform basin, margin, and slope facies with marked asymmetric distribution; the inner platform was locally emerged; 4) in the uppermost Dolomia Principale buildup margins become more abundant and the platform partially prograded on the basins; 5) at last the platform drowns and terrigenous sedimentation becomes prevalent (Riva di Solto Shales). The drowning of the platform is favoured by the lack of carbonate production, due to clay pollution and climatic changes in an area with high subsidence rates. The observed asymmetric distribution of buildup margins and fault-scarp related breccias, which outcrop on the western side of the basins west of Iseo Lake and bounding the eastern side of the basins east of Iseo Lake, allows us to propose a model of norian ensialic asymmetric rifting for the Lombardy Basin. This asymmetric rifting could be explained by interpreting the Lombardy Basin as a pull-apart basin, linked to transtension with E-W trending faults.